PEMBELAJARAN PENDIDIKAN AKHLAK SISWA SDN 01 PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Tarjuli Tarjuli (IAIN Bengkulu, 2020)
The study aims to describe the Learning of Moral Education Student Elementary School 01 Pondok Kelapa Central Bengkulu District. The objectives are detailed as follows: (1) Describe the planning of learning, (2) Implementation of Learn- ing Morals Education. (3) Evaluation of Learning Morals Education. This research is qualitative descriptive research with case study approach. The object of this studyis Learning Moral Education in review of planning, implementation, and evaluation at SDN 01 Pondok Kelapa, Central Bengkulu Regency. This research data comes from observation with field note notes (field notes), interviews, and documentation. Based on data analysis, it is known that in general, the learning of morality of students in SDN 01 Pondok Kelapa, Central Bengkulu Regency covers 3 main activities, namely: (1) Education Planning of Morals, (2) Implementation of Learning of Morals Education, and (3) Evaluation of Moral Learning. Learning planning includes the preparation of learning tools in the form of: a) 1. Formulating learning objectives, 2. Development of teaching materials, 3. Learning methods, 4. Learning media, 5. Resources / Materials teaching, 6. Evaluation. Learning implementation consists of: initial activities, core activities (learning activities) and final activities, c) evaluation consists of: 1. Written, oral, assignment, and observation test